Serpiginous choroiditis: a complex pharmacotherapeutic approach - Pal, Amitrajit A.; Joshi, Abhijeet D. (International Journal of Basic & Clinical Pharmacology, 2020)
Serpiginous choroiditis is a rare recurrent eye disorder which is characterized by formation of irregularly shaped (serpiginous) lesions involving two layers of the eye surface (the retinal pigment epithelium and the choriocapillaris). It is a rare clinical entity which causes less than 5% of posterior uveitis cases (3.9/1, 00,000 person-years). Diagnosing this rare disorder is a challenge in itself followed by its complex pharmacotherapeutic approach which is seen in the following case report. It will aid in bringing to light the various challenges faced in treatment to open a window for early diagnosis and better treatment regimens while keeping in mind the constant motivation and relaxed mind a patient needs to fight such a rare disease.